Mask Refills as a Measure of PAP Adherence - Scharf, Matthew T. (J Clin Sleep Med, 2017)
STUDY OBJECTIVES: Positive airway pressure (PAP) adherence data are a routine aspect of clinical care for obstructive sleep apnea (OSA), but not uniformly available. We hypothesized that mask refills are a measure of PAP adherence. METHODS: We measured PAP use over the first 90 days of treatment in 123 patients with OSA. The number and timing of mask refills was assessed over 18 months. Demographic and medical information was obtained from the electronic medical record. RESULTS: Average PAP use in the first week of more than 4 h/d was a predictor of adherence over the first 90 days (P < .0001). PAP use over 90 days was greater in datacard-derived data dependent on patients presenting a datacard to the clinic compared to modem-derived data (P = .0006). A mask refill within the first 30 days of treatment was associated with a 1.3 h/d lower PAP usage in the first 90 days (P = .0044). Conversely, the number of mask refills between 30 days and 18 months was associated with higher PAP adherence during the first 90 days, with an additional 0.61 h/d of use for each additional refill (P = .0015). CONCLUSIONS: In a retrospective cohort of veterans with OSA, first week PAP use was a strong predictor of 90-day use. Use of autonomously transmitted modem data avoided potential selection bias in adherence estimates. Mask refills in the first month were associated with less 90-day PAP use, whereas more mask refills after 30 days were associated with greater PAP use. CITATION: Scharf MT, Keenan BT, Pack AI, Kuna ST. Mask refills as a measure of PAP adherence. J Clin Sleep Med. 2017;13(11):1337–1344.